Comparative effectiveness of STEAM and CTL using MUSI board for cognitive understanding - Choirul Hadiyati; Achmad Buchori; Joko Siswanto (Indonesian Journal of Educational Development (IJED), 2026)
Elementary students continue to struggle to understand Least Common Multiple (LCM) and Greatest Common Factor (GCF), highlighting the need for more effective instructional approaches that promote conceptual understanding. Although Science, Technology, Engineering, Arts, and Mathematics (STEAM) and Contextual Teaching and Learning (CTL) have shown positive outcomes, direct comparisons with the same instructional medium remain limited. This study's novelty is the direct comparison of STEAM and CTL using the same manipulative instructional medium (MUSI Board), isolating instructional effects from learning media. Therefore, this study aimed to compare the effectiveness of STEAM and CTL using the MUSI Board to improve cognitive understanding of LCM and GCF. A quasi-experimental pretest–posttest non-equivalent group design involved 30 fifth-grade students assigned through matched-group sampling to STEAM (n = 15) and CTL (n = 15). Data were analyzed using t-tests, normalized gain (N-Gain), and Cohen's d. Both groups improved significantly (p < .001), but STEAM achieved higher learning gains (0.487 vs. 0.352) with a very large educational effect (Cohen's d = 1.975). Conceptually, the findings strengthen evidence on the comparative effectiveness of STEAM and CTL. Practically, MUSI Board-assisted STEAM is recommended for elementary mathematics, while future studies should examine broader topics using larger samples.